2022
DOI: 10.24843/eeb.2022.v11.i09.p03
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Daya Saing Dan Faktor Yang Memengaruhi Nilai Ekspor Komoditas Timah Indonesia Di Pasar Internasional

Abstract: This study aims to analyze the competitiveness of Indonesian tin export commodities in the international market, the direct effect of exchange rates and international prices on the value of Indonesian tin exports, the direct effect of exchange rates, international prices, and export values ??on the competitiveness of Indonesian tin, and to determine the relationship between exchange rates and international prices indirectly affect the competitiveness of Indonesian tin. This research was conducted in the range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 1 publication
0
0
0
1
Order By: Relevance
“…Research [21] states that Exchange rate variables have a significant impact on Indonesia's coal exports. In contrast to research conducted by [15] concluded that the exchange rate has no direct effect on the value of Indonesian tin exports. In other words, when the exchange rate increases, the value of tin exports does not increase.…”
Section: Literature Reviewcontrasting
confidence: 65%
See 2 more Smart Citations
“…Research [21] states that Exchange rate variables have a significant impact on Indonesia's coal exports. In contrast to research conducted by [15] concluded that the exchange rate has no direct effect on the value of Indonesian tin exports. In other words, when the exchange rate increases, the value of tin exports does not increase.…”
Section: Literature Reviewcontrasting
confidence: 65%
“…Based on the research conducted by [12] states that the nickel commodity export price variables have a positive effect on nickel export value, in which the price of each nickel item i ncreases by 1%, it will increase the value of nickel exports. In addition, research results from [15] indicate that global prices positively and significantly impact the export value of Indonesian tin. The increasing production volume of a commodity will certainly affect its export value.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A country can specialize in manufacturing goods and services more cheaply both in terms of costs and resources as well as how to produce through specializing, thanks to the various benefits that come with international trade [3]. In order to employ Indonesia's natural resources in international commerce activities where they are used to fulfill the demands of other nations [4].…”
Section: Introductionmentioning
confidence: 99%
“…Faktor penting untuk mendorong produksi kopi yaitu luas lahan yang memadai (Purba, 2011). Peningkatan permintaan kopi tidak sebanding dengan produksi kopi yang menurun sehingga produktivitas kopi tidak signifikan (Sihotang, 2013).…”
unclassified